Pengaruh Jumlah Penduduk Dan Pengangguran Terhadap Tingkat Kemiskinan Di Kabupaten Tolitoli - Hilmi, Hilmi; Nasir, Moh; Ramlawati, Ramlawati; Peuru, Cytra Dewi (GROWTH Jurnal Ilmiah Ekonomi Pembangunan, 2022)
This study aims to determine the effect of population and unemployment on the level of poverty in Tolitoli Regency. This study uses a quantitative research design. Sources of data in the form of secondary data, namely data obtained through documentation related to this research. The data analysis technique used is time series data analysis with multiple linear regression. Based on the results of the research and discussion, it can be concluded that the population variable has no significant positive effect on the poverty level of 0.006%, while the unemployment variable has an insignificant negative effect on the poverty level of -0.606. Simultaneously the two variables are not significant to the poverty level.